New aspects of the influence of immunity and microbiome on heart transplant rejection - A. S. Golovkin; I. V. Kudryavtsev; P. A. Fedotov; O. V. Kalinina (Российский кардиологический журнал, 2022)
Currently, heart transplantation is the key treatment for patients with end-stage heart failure. At the same time, the immunopathogenesis of chronic allograft rejection, which is a key factor in the long-term outcome, is still poorly understood, which, in turn, explains the absence of effective non-invasive methods for its detection. This review discusses up-to-date aspects of the interaction between the microbiota and immune system factors leading to inflammation and T-cell polarization, and their participation in heart transplant rejection. Special attention is paid to the role of microvesicles in immune response modulation within heart transplant rejection.